Edukasi Peningkatan Kreativitas Anak Jalanan Masa Pandemi Covid-19 melalui Media Online - Imelda; Indah Rahayu Lestari; Rinny Meidiyustiani (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2022)
Street children are the nation's future assets. Ironically, the street children are neglected. The Save Street Child Foundation, one of the shelters that became “Our School” in Pondok Ranji, Tangerang, is a place that street children rely on. However, the existence of this Foundation is still limited and has not been able to fully meet the needs of children. The problems faced by street children are lack of motivation to learn, lack of awareness of parents about the importance of children's education, environmental factors of children that are not conducive to child development. This Community Service activity is aimed at street children at the Save Street Child Foundation. This service aims to increase the creativity of the Save Street Child Foundation street children during the Covid-19 Pandemic through online media. The stages of service include: determining the location, interview/discussion with the principal and teacher of the Save Street Child Foundation, conducting field observations, problem analysis, preparation, implementation and evaluation. The types of creativity activities carried out include: socialization of health protocols, education on watching films, education on coloring competitions, planting tree seeds, education in English, Origami Creativity, Handicrafts from Flannel. Some of the information from this activity was taken, learned from the online media Youtube to street children. When education is carried out, street children enjoy learning methods taken from the online media Youtube.